Analysis of The Implementation of Tax Planning on Article 21 Income Tax as An Effort to Optimize Tax Burden Efficiency at PT. Anugerah Sejahtera - ADYATMA, I Wayan Chandra; NIDA, Desak Rurik Pradnya Paramitha (Journal of Governance, Taxation and Auditing, 2024)
Taxes are a very important component for every country, because taxes play a major role in state financing and national development which aims to improve the welfare of the people. Through good tax planning, PT Anugerah Sejahtera can carry out tax payments more efficiently while still complying with applicable tax regulations. In an effort to achieve this efficiency, there are several tax planning methods that can be used, namely the Net Method, Gross Method, and Gross Up Method. Through analysis of the application of these three methods, it is hoped that the most efficient tax payment method will be found and can simplify the tax calculation and deduction process. This research aims to determine the effectiveness of implementing article 21 income tax planning using the Net, Gross, and Gross Up methods at PT. Anugerah Sejahtera. The type of research that will be applied in this research is descriptive qualitative. Based on the research results, the Gross Up method is proven to be the most efficient method for paying Article 21 income tax. This is because there are tax allowances which provide positive benefits for the company. Applying the Gross Up method also affects the company's income tax burden and net profit, because this additional tax allowance reduces the company's taxable income.